A ferroelectric modified positive electrode material and preparation method thereof and secondary battery
By freeze-drying and high-temperature heat treatment of ferroelectric materials with metal oxide precursors or positive electrode materials, ferroelectric modified positive electrode materials are prepared, which solves the problems of complex process, high cost and insignificant effects in the prior art, and achieves high stability and excellent cycling performance.
Patent Information
- Application Number
- CN202310063043.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-01-17
AI Technical Summary
In the prior art, the method of ferroelectric for modification of positive electrode materials has problems such as complex process, high cost and insignificant effects, making it difficult to achieve engineering application.
By dispersing the ferroelectric material in water, adding a metal oxide precursor or a positive electrode material, lyophilized drying and ball milling, and then undergoing high-temperature heat treatment, a ferroelectric modified positive electrode material with dense, uniform and stable are prepared.
This method can effectively improve the interface structure stability of the positive electrode material, improve the cycle life and rate performance of the secondary battery, and has the advantages of low cost, simple operation and environmentally friendly, and is suitable for large-scale engineering preparation and application.
Smart Images

Figure HDA0004061508710000011 
Figure HDA0004061508710000012 
Figure HDA0004061508710000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new energy materials and devices, and relates to a ferroelectric modified positive electrode material and a preparation method thereof and a secondary battery. Background Art
[0002] As the main technical form of electrochemical energy storage, secondary batteries play an important role in the development and utilization of renewable energy, the change of grid load structure and the development of the global power market environment. The research and development of high-capacity cathode materials is the key to the development of the next generation of high-energy-density secondary batteries. However, in the process of engineering application of high-capacity cathode materials, there are generally technical problems related to the stability of the surface and interface structure that need to be solved urgently.
[0003] Ferroelectrics are increasingly used in electronics, biomedicine, energy storage, catalysis and other fields due to their large dielectric constant, low dielectric loss and strong pressure resistance. The non-centrosymmetric crystal structure of ferroelectrics will form electric dipoles inside, so that they can spontaneously polarize and orient with the change of the external electric field environment, generating an internal polarization electric field. Compared with traditional modification methods, the above-mentioned unique physical properties of ferroelectrics can effectively improve the surface and interface stability of positive electrode materials. However, the current research on the modification of positive electrode materials based on ferroelectric polarization electric fields is mainly based on thin film preparation processes such as magnetron sputtering and laser pulse deposition or liquid phase coating. Since the application scenarios of thin film modification processes are very limited and can only be used for the entire electrode or the surface of the electrode, it is difficult to modify or protect the inside of the electrode. Liquid phase coating has serious coating uniformity problems. It is easy to form an "island-like" coating layer during the early heating treatment of the liquid phase method and the thermal decomposition and crystallization of the ferroelectric precursor, and the modification effect is difficult to control. Therefore, the above modification methods still have disadvantages such as complex process, high cost, and unclear effect, which makes it difficult to realize engineering application, and there are few related patent reports. Summary of the invention
[0004] In order to solve the problems of the above-mentioned prior art, the present invention provides a ferroelectric modified positive electrode material and a preparation method thereof and a secondary battery. The method has the characteristics of simple process, low cost and effective improvement of the surface and interface structural stability of the positive electrode material. Based on the prepared positive electrode material, a secondary battery with long cycle life and high rate performance can be obtained, which has very good engineering application prospects.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a ferroelectric modified positive electrode material comprises the following steps:
[0007] Step 1, dispersing a ferroelectric material in water to obtain a dispersion 1;
[0008] Step 2, dispersing a metal oxide precursor in dispersion 1 to obtain dispersion 2;
[0009] Step 3: Freeze-dry and pulverize the dispersion liquid 2 to obtain a freeze-dried powder.
[0010] Step 4: Ball-mill and mix the freeze-dried powder with an alkali metal salt to obtain a mixture.
[0011] Step 5: Heat-treat the mixture to obtain a ferroelectric-modified cathode material.
[0012] Alternatively, it includes the following steps:
[0013] Step 1: Disperse the ferroelectric material in water to obtain a dispersion liquid 1.
[0014] Step 2: Disperse the cathode material in the dispersion liquid 1 to obtain a dispersion liquid 2.
[0015] Step 3: Freeze-dry and pulverize the dispersion liquid 2 to obtain a freeze-dried powder.
[0016] Step 4: Heat-treat the freeze-dried powder to obtain a ferroelectric-modified cathode material.
[0017] Preferably, the ferroelectric material is one or more of ABO3, ZnO, and HrO2; wherein, in ABO3, A is Li, La, Bi, Ba, Ca, Er, Sr, or Pb, and B is Ti, Nb, Zr, Fe, Mg, or Mn.
[0018] Preferably, the metal oxide precursor is an oxide of one or more of Ni, Co, Mn, Fe, Nb, Ti, V, Mo, and Cr.
[0019] Preferably, the alkali metal salt is one of LiNO3, NaNO3, KNO3, LiOH, NaOH, KOH, Li2CO3, Na2CO3, K2CO3, CH3COOLi, CH3COONa, CH3COOK, LiCl, NaCl, and KCl.
[0020] Preferably, the ball-milling time is 1 - 24 h, and the mass ratio of balls to materials used is (1 - 200):1.
[0021] Preferably, the cathode material is one or more of N x MO2, N x M2O4, and N[N y M 1-y O2, where 0 < x < 1.05, M is one or more of Ni, Co, Mn, Fe, Nb, Ti, V, Mo, and Cr, N is Li, Na, or K, and 0 < y < 1.
[0022] Preferably, the mass ratio of the ferroelectric material to the metal oxide precursor or the positive electrode material is (0.01-10):1.
[0023] Preferably, the heat treatment is carried out in air or oxygen atmosphere, the heat treatment temperature is 300-1200° C., and the time is 5-48 hours.
[0024] The ferroelectric modified positive electrode material is obtained by the preparation method.
[0025] A secondary battery comprises the ferroelectric modified positive electrode material.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The method of the present invention is to prepare ferroelectric nanoparticles (particle size <10nm) into a uniform dispersion; after the dispersion is uniformly mixed with a metal oxide precursor, it is subjected to freeze drying treatment. Since the ferroelectric nanoparticles can avoid agglomeration under a low-temperature vacuum environment, they can be uniformly adsorbed in the micro-nano structure of the precursor surface layer, and after complete drying, a metal oxide precursor with modified ferroelectric surface is obtained; the metal oxide precursor with modified ferroelectric surface is mixed with an alkali metal salt, and subjected to high-temperature calcination to obtain a ferroelectric modified positive electrode material with compactness, uniformity and good stability, or the ferroelectric nanoparticle dispersion is mixed with a positive electrode material, and subjected to freeze drying and heat treatment to obtain a ferroelectric modified positive electrode material. The present invention uses freeze drying to treat the modified precursor or positive electrode material. Compared with the prior art, this method can inhibit the agglomeration of ferroelectric nanoparticles during the drying process, is conducive to the uniform dispersion of ferroelectrics on the surface and inside the bulk of the precursor or positive electrode material, and has an improvement effect on the uniform distribution of the polarization electric field of the ferroelectric and its free radical adsorption. Compared with traditional methods such as surface coating and doping modification, the present invention has the advantages of low cost, simple operation, environmental friendliness, and easy process repeatability, and has obvious advantages in large-scale engineering preparation and application.
[0028] The ferroelectric modified positive electrode material prepared by the method of the present invention has excellent surface structural stability. The ferroelectrics on the surface of the positive electrode material and inside the bulk phase generate a polarization electric field during the charge and discharge process, effectively adsorb free radicals generated by the decomposition of the electrolyte and the positive electrode material, and inhibit their further decomposition, thereby greatly improving the electrode cycle stability and enhancing the cycle life of the secondary battery. The material can be used to prepare secondary batteries with excellent cycle performance and rate performance.
[0029] The ferroelectric modified positive electrode material prepared by the present invention is used in secondary batteries, exhibits excellent cycle stability, and greatly improves the battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1The LiNi used in Example 1 of the present invention 0.5 Mn 0.5 SEM image of O2 cathode material;
[0031] Figure 2 The BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 SEM image of O2 composite material;
[0032] Figure 3 a is BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 O2 composite TEM images; bf are BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 Element mapping diagram of O2 composite material;
[0033] Figure 4 The BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 SEM image of O2 cathode material;
[0034] Figure 5 The BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 XRD pattern of O2 cathode material;
[0035] Figure 6 a is BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 TEM images of O2 positive electrode materials, bf are BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 Element mapping diagram of O2 cathode material;
[0036] Figure 7 The BaTiO3 / LiNi prepared in Example 3 of the present invention 0.85 Mn 0.05 Co 0.1 SEM image of O2 cathode material;
[0037] Figure 8 The BaTiO3 / Li prepared in Example 8 of the present invention 1.2 Ni 0.2 Mn 0.6 SEM image of O2 cathode material;
[0038] Fig. 9 The BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5Mn 0.5 O2 and SrTiO3 / LiNi prepared in comparative example 0.5 Mn 0.5 Cycling performance diagram of O2 positive electrode material as positive electrode of lithium-ion battery. DETAILED DESCRIPTION
[0039] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.
[0040] A method for modifying positive electrode materials based on ferroelectric polarization electric field comprises the following steps:
[0041] Step 1, adding ferroelectric material into deionized water, stirring or ultrasonicating, to obtain dispersion 1;
[0042] Step 2, adding a metal oxide precursor or a positive electrode material to the dispersion 1 in step 1, and stirring to obtain a dispersion 2;
[0043] Step 3, freeze-drying the dispersion 2 obtained in step 2, and then grinding it evenly to obtain a freeze-dried powder;
[0044] Step 4, ball-milling the freeze-dried powder and the alkali metal salt to obtain a mixture. If the positive electrode material is added in step 2, this step is not required;
[0045] Step 5, subjecting the freeze-dried powder of step 3 or the mixture obtained in step 4 to high-temperature heat treatment to obtain a ferroelectric-modified positive electrode material.
[0046] In step 1, the ferroelectric material is one or more of ABO3 (A is Li, La, Bi, Ba, Ca, Er, Sr or Pb; B is Ti, Nb, Zr, Fe, Mg or Mn), ZnO, HrO2, the concentration of dispersion 1 is 0.0001~0.1g / mL, and the single particle size of the ferroelectric material is 5~500nm.
[0047] In step 2, the mass ratio of the ferroelectric material to the metal oxide precursor or the positive electrode material is (0.01-10):1, and the concentration of the ferroelectric material to the metal oxide precursor or the positive electrode material dispersion is 0.0001-0.1 g / mL. The metal oxide precursor is a +2, +3, +4 or +5 valent oxide of the metal element Ni, Co, Mn, Fe, Nb, Ti, V, Mo or Cr; if the positive electrode material is added, it is a layered structure of N x MO2 and / or spinel structured N x M2O4 and / or composite structure N[N y M 1-yO2, where 0 < x < 1.05, M is one or more of Ni, Co, Mn, Fe, Nb, Ti, V, Mo, and Cr; N is Li, Na, or K; 0 < y < 1.
[0048] In step 4, the alkali metal lithium used is one of LiNO3, NaNO3, KNO3, LiOH, NaOH, KOH, Li2CO3, Na2CO3, K2CO3, CH3COOLi, CH3COONa, CH3COOK, LiCl, NaCl, and KCl. The ball milling is planetary ball milling, the ball milling mixing time is 1 - 24 h, and the ball - to - material mass ratio is (1 - 200):1. If the positive electrode material is added in step 2, this step is not required.
[0049] In step 5, the heat treatment process is carried out in a muffle furnace / cabinet furnace with an air / oxygen atmosphere. The heat treatment temperature is 300 - 1200 °C, and the holding time is 5 - 48 h.
[0050] The X - ray diffraction (XRD) characteristic peaks of the ferroelectric - modified positive electrode material prepared by the above steps belong to monoclinic, rhombohedral, hexagonal, cubic, and tetragonal crystal phases. Ferroelectric nanoparticles are distributed in the surface layer with a depth of 1 - 200 nm and in the bulk phase. The prepared ferroelectric - modified positive electrode material is used as an active substance in energy conversion and storage, photocatalysis, electrocatalysis, photoelectrocatalysis, and gas sensing.
[0051] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments of the present invention. All raw materials are of analytical purity.
[0052] Example 1:
[0053] Step 1, add 0.001 g of BaTiO3 to 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0054] Step 2, add 0.2 g of LiNi 0.5 Mn 0.5 O2 positive electrode material to the dispersion in step 1, continue to stir for 5 min, then ultrasonic disperse for 5 min, and alternately repeat the above process three times to obtain a uniform mixture dispersion;
[0055] Step 3, put the dispersion obtained in step 2 into dry ice and freeze for 30 min. After the dispersion is completely frozen, transfer it to a freeze - dryer, cool down to - 60 °C, and obtain BaTiO3 / LiNi 0.5 Mn 0.5 O2 composite after freeze - drying for 48 h;
[0056] Step 4, putting the composite material obtained in step 3 into a muffle furnace, heating it to 500°C at a heating rate of 5°C / min, keeping it warm for 5 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain a ferroelectric modified positive electrode material.
[0057] Figure 1 It is the LiNi added in step 2 0.5 Mn 0.5 SEM image of O2 cathode material. From the image, we can see that LiNi 0.5 Mn 0.5 The O2 particles have high crystallinity and the grain size distribution is between 200 and 500 nm.
[0058] Figure 2 It is BaTiO3 / LiNi obtained in step 3 0.5 Mn 0.5 SEM image of O2 composite material. From the image, we can see that after freeze-drying and BaTiO3 composite, the particle size and crystallinity of the positive electrode material are not affected.
[0059] Figure 3 It is BaTiO3 / LiNi obtained in step 3 0.5 Mn 0.5 TEM image of O2 composite material. It can be clearly seen from the figure that the positive electrode material after ferroelectric modification is composed of Ni, Mn, O, Ba and Ti elements and is evenly distributed, indicating that there is no agglomeration of ferroelectrics on the surface and in the bulk of the positive electrode material. The evenly distributed ferroelectrics can ensure faster ion migration power on the surface interface and in the bulk during the charge and discharge process of the positive electrode material, while inhibiting the free radicals generated by the surface interface electrolyte and the positive electrode material, which can effectively improve the stability of the positive electrode.
[0060] Figure 4 It is BaTiO3 / LiNi obtained in step 4 0.5 Mn 0.5 SEM image of O2 positive electrode material. From the image, we can see that the morphology of the modified positive electrode material is not damaged, and the angular crystal structure can be observed.
[0061] Figure 5 BaTiO3 / LiNi obtained in step 4 0.5 Mn 0.5 O2 composite material XRD diagram, from which we can see that the positive electrode material still has LiNi after modification 0.5 Mn 0.5 The original layered phase structure of O2.
[0062] Figure 6 It is BaTiO3 / LiNi obtained in step 4 0.5 Mn 0.5TEM image of O2 composite material. It can be clearly seen from the image that the positive electrode material after ferroelectric modification is composed of Ni, Mn, O, Ba and Ti elements and is evenly distributed, and is not affected by subsequent heat treatment.
[0063] Embodiment 2:
[0064] Step 1, add 0.01 g of LaTiO3 into 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0065] Step 2: 0.2 g of LiTi 0.5 Mn 0.5 The O2 positive electrode material is added to the dispersion in step 1, and the mixture is stirred for 5 minutes, and then ultrasonically dispersed for 5 minutes, and the above process is repeated three times to obtain a uniform mixture dispersion;
[0066] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes. After the dispersion is completely frozen, it is moved into a freeze dryer, cooled to -60°C, and freeze-dried for 48 hours to obtain LaTiO3 / LiTi 0.5 Mn 0.5 O2 composite material;
[0067] Step 4, putting the composite material obtained in step 3 into a muffle furnace, heating it to 800°C at a heating rate of 5°C / min, keeping it warm for 12 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain a ferroelectric modified positive electrode material.
[0068] XRD, SEM and TEM analysis showed that the product obtained in Example 2 was LaTiO3 / LiTi 0.5 Mn 0.5 O2 ferroelectric modified positive electrode material. It is composed of Ni, Mn, O, Ba and Ti elements and is evenly distributed. The phase is accurate and the evenly distributed ferroelectric can ensure faster ion migration power at the surface interface and in the bulk phase, while effectively improving the stability of the positive electrode.
[0069] Embodiment 3:
[0070] Step 1, add 2 g of Li2NbO3 into 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0071] Step 2: 0.2 g of Ni 0.85 Mn 0.05 Co 0.1 The (OH)2 precursor was added to the dispersion in step 1, and the mixture was stirred for 5 min, and then ultrasonically dispersed for 5 min, and the above process was repeated three times to obtain a uniform mixture dispersion.
[0072] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes, and after the dispersion is completely frozen, it is moved into a freeze dryer, cooled to -60°C, and freeze-dried for 48 hours to obtain Li2NbO3 / Ni 0.85 Mn 0.05 Co 0.1 (OH)2 composites;
[0073] Step 4: The composite material obtained in step 3 is treated according to the chemical formula LiNi 0.85 Mn 0.05 Co 0.1 The stoichiometric ratio of O2 was added with Li2CO3 in excess of 5%, the ball-to-material mass ratio was 20:1, and the mixture was mixed by planetary ball mill for 4 h to obtain a uniform mixture;
[0074] Step 5, put the mixture obtained in step 4 into a tubular furnace, introduce oxygen at a rate of 30 mL / min, heat it to 500°C at a heating rate of 5°C / min, keep it warm for 5 hours, heat it to 900°C at a heating rate of 5°C / min, keep it warm for 28 hours, cool it naturally to room temperature, take it out, grind it evenly, and obtain a ferroelectric modified positive electrode material.
[0075] XRD, SEM and TEM analysis showed that the product obtained in Example 3 was rhombohedral Li2NbO3 / hexagonal LiNi 0.85 Mn 0.05 Co 0.1 O2 ferroelectric modified positive electrode material. It is composed of Ni, Co, Mn, O, Ba and Ti elements and is evenly distributed. The phase is accurate and the evenly distributed ferroelectric can ensure faster ion migration power at the surface interface and in the bulk phase, while effectively improving the stability of the positive electrode.
[0076] Figure 7 Li2NbO3 / LiNi prepared in this example 0.85 Mn 0.05 Co 0.1 From the SEM image of the O2 positive electrode material, we can see that the positive electrode material particles are uniform and complete, and are mainly composed of micron-sized secondary spherical particles assembled from primary particles.
[0077] Embodiment 4:
[0078] Step 1, add 0.2 g of BiFeO3 into 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0079] Step 2: 0.2 g of Ni 0.1 Mo 0.1 Mn 0.6The O3 precursor was added to the dispersion in step 1, and the mixture was stirred for 5 min, and then ultrasonically dispersed for 5 min, and the above process was repeated three times to obtain a uniform mixture dispersion.
[0080] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes. After the dispersion is completely frozen, it is moved into a freeze dryer, cooled to -60°C, and freeze-dried for 48 hours to obtain BiFeO3 / Ni 0.1 Mo 0.1 Mn 0.6 O3 composite material;
[0081] Step 4: the composite material obtained in step 3 is treated according to the chemical formula Li 1.2 Ni 0.1 Mo 0.1 Mn 0.6 The stoichiometric ratio of O2 was 5% in excess of LiCl, the ball-to-material mass ratio was 20:1, and the mixture was mixed by planetary ball milling for 4 h to obtain a uniform mixture;
[0082] Step 5, putting the mixture obtained in step 4 into a muffle furnace, heating it to 800°C at a heating rate of 5°C / min, keeping it warm for 12 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain a ferroelectric modified positive electrode material.
[0083] XRD, SEM and TEM analysis showed that the product obtained in Example 4 was tetragonal BiFeO3 / rhombohedral Li 1.2 Ni 0.1 Mo 0.1 Mn 0.6 O2 ferroelectric modified positive electrode material. It is composed of Ni, Mo, Mn, O, Ba and Ti elements and is evenly distributed. The phase is accurate and the evenly distributed ferroelectric can ensure faster ion migration power at the surface interface and in the bulk phase, while effectively improving the stability of the positive electrode.
[0084] Embodiment 5:
[0085] Step 1, 0.002 g of ZnO was added to 40 mL of deionized water (concentration was 0.05 mg / mL), and a uniform dispersion was obtained after ultrasonic dispersion for 30 min;
[0086] Step 2: 0.2 g of Ni 0.5 Mn 1.5 O 3.5 The precursor was added to the dispersion in step 1, and the mixture was stirred for 5 min, and then ultrasonically dispersed for 5 min, and the above process was repeated three times to obtain a uniform mixture dispersion.
[0087] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes, and after the dispersion is completely frozen, it is moved into a freeze dryer, cooled to -60°C, and freeze-dried for 48 hours to obtain ZnO / Ni 0.5 Mn 1.5 O 3.5 Composite materials;
[0088] Step 4: The composite material obtained in step 3 is treated according to the chemical formula LiNi 0.5 Mn 1.5 The stoichiometric ratio of O4 was added with LiOH in excess of 5%, the ball-to-material mass ratio was 20:1, and the mixture was mixed by planetary ball mill for 4 h to obtain a uniform mixture;
[0089] Step 5, putting the mixture obtained in step 4 into a muffle furnace, heating it to 900°C at a heating rate of 5°C / min, keeping it warm for 48 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain a ferroelectric modified positive electrode material.
[0090] XRD, SEM and TEM analysis showed that the product obtained in Example 5 was a four-directional ZnO / cubic phase LiNi 0.5 Mn 1.5 O4 ferroelectric modified positive electrode material. It is composed of Ni, Mn, O and Zn elements and is evenly distributed. The phase is accurate and the evenly distributed ferroelectric can ensure faster ion migration power at the surface interface and in the bulk phase, while effectively improving the stability of the positive electrode.
[0091] Embodiment 6:
[0092] Step 1, add 0.002 g of HrO2 into 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0093] Step 2: 0.2 g of Ni 0.2 Mn 0.6 The O3 precursor was added to the dispersion in step 1, and the mixture was stirred for 5 min, and then ultrasonically dispersed for 5 min, and the above process was repeated three times to obtain a uniform mixture dispersion.
[0094] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes. After the dispersion is completely frozen, it is moved into a freeze dryer, cooled to -60°C, and freeze-dried for 48 hours to obtain HrO2 / Ni 0.2 Mn 0.6 O3 composite material;
[0095] Step 4: the composite material obtained in step 3 is treated according to the chemical formula Li 0.2 Na 0.6 Ni 0.2 Mn 0.6LiNO3 and Na2CO3 were added to the stoichiometric ratio of O2 with an excess of 5%, and the ball-to-material mass ratio was 20:1, and the mixture was mixed by planetary ball mill for 4 h to obtain a uniform mixture;
[0096] Step 5, putting the mixture obtained in step 4 into a muffle furnace, heating it to 1200°C at a heating rate of 5°C / min, keeping it warm for 36 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain a ferroelectric modified positive electrode material.
[0097] XRD, SEM and TEM analysis showed that the product obtained in Example 6 was HrO2 / Li 1.2 Ni 0.2 Mn 0.6 O2 ferroelectric modified positive electrode material. It is composed of Ni, Mn, O, and Hr elements and is evenly distributed. The phase is accurate and the evenly distributed ferroelectric can ensure faster ion migration power at the surface interface and in the bulk phase, while effectively improving the stability of the positive electrode.
[0098] Embodiment 7:
[0099] Step 1, add 0.002 g of LaMnO3 into 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0100] Step 2: 0.2 g of NaNi 0.5 Mn 0.5 The O2 positive electrode material is added to the dispersion in step 1, and the mixture is stirred for 5 minutes, and then ultrasonically dispersed for 5 minutes, and the above process is repeated three times to obtain a uniform mixture dispersion;
[0101] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes. After the dispersion is completely frozen, it is moved into a freeze dryer and cooled to -60°C. After freeze drying for 48 hours, tetragonal LaMnO3 / hexagonal NaNi 0.5 Mn 0.5 O2 composite material;
[0102] Step 4, putting the composite material obtained in step 3 into a muffle furnace, heating it to 500°C at a heating rate of 5°C / min, keeping it warm for 5 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain a ferroelectric modified positive electrode material.
[0103] XRD, SEM and TEM analysis showed that the product obtained in Example 7 was LaMnO3 / NaNi 0.5 Mn 0.5O2 ferroelectric modified positive electrode material. It is composed of La, Ni, Mn, O, Ba and Ti elements and is evenly distributed. The phase is accurate and the evenly distributed ferroelectric can ensure faster ion migration power at the surface interface and in the bulk phase, while effectively improving the stability of the positive electrode.
[0104] Example 8
[0105] Step 1, add 0.001 g of BaTiO3 into 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0106] Step 2: 0.2 g of LiNi 0.5 Mn 1.5 The O4 positive electrode material is added to the dispersion in step 1, and the mixture is stirred for 5 minutes, and then ultrasonically dispersed for 5 minutes, and the above process is repeated three times to obtain a uniform mixture dispersion;
[0107] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes, and after the dispersion is completely frozen, it is moved into a freeze dryer, cooled to -60°C, and freeze-dried for 48 hours to obtain BaTiO3 / LiNi 0.5 Mn 1.5 O4 composite material;
[0108] Step 4, putting the composite material obtained in step 3 into a muffle furnace, heating it to 500°C at a heating rate of 5°C / min, keeping it warm for 5 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain a ferroelectric modified positive electrode material.
[0109] Figure 8 The BaTiO3 / LiNi prepared in this example 0.5 Mn 1.5 SEM image of O4 positive electrode material. From the image, we can see that the positive electrode material particles are uniform and complete, and are mainly composed of Ni, Mn, O, Ba and Ti elements.
[0110] Example 9
[0111] Step 1, add 0.001 g of BaTiO3 into 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0112] Step 2: 0.2 g of Li[Li 0.2 Ni 0.2 Mn 0.6 ] Add the O2 positive electrode material to the dispersion in step 1, continue stirring for 5 minutes, then ultrasonically disperse for 5 minutes, and repeat the above process three times alternately to obtain a uniform mixture dispersion;
[0113] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes. After the dispersion is completely frozen, it is moved into a freeze dryer, cooled to -60°C, and freeze-dried for 48 hours to obtain BaTiO3 / LiNi 0.5 Mn 1.5 O4 composite material;
[0114] Step 4, putting the composite material obtained in step 3 into a muffle furnace, heating it to 500°C at a heating rate of 5°C / min, keeping it warm for 5 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain a ferroelectric modified positive electrode material.
[0115] Comparative Example:
[0116] Step 1, add 0.002 g of SrTiO3 into 40 mL of deionized water (concentration is 0.05 mg / mL), and obtain a uniform dispersion after ultrasonic dispersion for 30 min;
[0117] Step 2: 0.2 g of Ni 0.5 Mn 0.5 The O3 precursor was added to the dispersion in step 1, and the mixture was stirred for 5 min, and then ultrasonically dispersed for 5 min, and the above process was repeated three times to obtain a uniform mixture dispersion.
[0118] Step 3, the dispersion obtained in step 2 is placed in dry ice and frozen for 30 minutes, and after the dispersion is completely frozen, it is moved into a freeze dryer, cooled to -60°C, and freeze-dried for 48 hours to obtain SrTiO3 / Ni 0.5 Mn 0.5 O3 composite material;
[0119] Step 4: The composite material obtained in step 3 is treated according to the chemical formula LiNi 0.5 Mn 0.5 The stoichiometric ratio of O2 was 5% in excess of LiOH, the ball-to-material mass ratio was 20:1, and the mixture was mixed by planetary ball milling for 4 h to obtain a uniform mixture;
[0120] Step 5, putting the mixture obtained in step 4 into a muffle furnace, heating it to 800°C at a heating rate of 5°C / min, keeping it warm for 12 hours, cooling it naturally to room temperature, taking it out, and grinding it evenly to obtain ferroelectric modified SrTiO3 / LiNi 0.5 Mn 0.5 O2 positive electrode material.
[0121] Test example:
[0122] The modified positive electrode material is applied to lithium-ion batteries: the BaTiO3 / LiNi 0.5 Mn 0.5O2 positive electrode material, conductive carbon black and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, nitrogen methyl pyrrolidone (NMP) was added and stirred evenly, then coated on aluminum foil and dried in a vacuum oven at 80°C for 6 h to obtain a positive electrode sheet. Metallic lithium was used as the counter electrode, 1M lithium hexafluorophosphate (LiPF6) was dissolved in equal volumes of ethylene carbonate (EC) and dimethyl carbonate (DMC) as the electrolyte, and porous monolayer polypropylene (Celgard2500) was used as the diaphragm. A CR2025 lithium-ion battery was assembled in an argon-filled glove box to test its electrochemical properties.
[0123] Battery performance test conditions: metal lithium as counter electrode, voltage window 2.7-4.3V (vs.Li + / Li), and the rate size used in the cycle performance test was 1.0C.
[0124] Fig. 9 The BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 O2 and SrTiO3 / LiNi prepared in comparative example 0.5 Mn 0.5 O2 are the positive electrodes of lithium-ion batteries, and the cycle performance diagram tested at a rate of 1.0C. As can be seen from the figure, the BaTiO3 / LiNi prepared in Example 1 of the present invention 0.5 Mn 0.5 After 100 cycles, the positive electrode of O2 still has a capacity of 170mAh / g, which is significantly higher than that of the comparative example SrTiO3 / LiNi 0.5 Mn 0.5 The electrochemical capacity of the O2 positive electrode after 100 cycles shows that compared with the non-ferroelectric material SrTiO3 modified LiNi 0.5 Mn 0.5 O2 positive electrode, LiNi modified by ferroelectric material BaTiO3 0.5 Mn 0.5 The O2 cathode has excellent cycling stability.
[0125] The above is only one embodiment of the present invention, not all or the only embodiment. Any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the specification of the present invention are covered by the claims of the present invention.
Claims
1. A method for preparing a ferroelectric modified positive electrode material, characterized in that: The following steps are involved: Step 1, dispersing a ferroelectric material with a particle size of less than 10 nm in water to obtain a dispersion 1; Step 2, dispersing a metal oxide precursor in dispersion 1 to obtain dispersion 2; Step 3, freeze-drying and crushing the dispersion 2 to obtain a freeze-dried powder; Step 4, mixing the freeze-dried powder and the alkali metal salt by ball milling to obtain a mixture; Step 5, heat treating the mixture to obtain a ferroelectric modified positive electrode material; Alternatively, include the following steps: Step 1, dispersing a ferroelectric material with a particle size of less than 10 nm in water to obtain a dispersion 1; Step 2, dispersing the positive electrode material in dispersion 1 to obtain dispersion 2; Step 3, freeze-drying and crushing the dispersion 2 to obtain a freeze-dried powder; Step 4, heat-treating the freeze-dried powder to obtain a ferroelectric-modified positive electrode material; Wherein, the ferroelectric material is one or more of ABO3 and ZnO; wherein, A in ABO3 is Li, La, Bi, Ba, Ca, Er, Sr or Pb, and B is Ti, Nb, Zr, Fe, Mg or Mn; the metal oxide is one or more of Ni, Co, Mn, Fe, Nb, Ti, V, Mo and Cr; the alkali metal salt is one of LiNO3, NaNO3, KNO3, LiOH, NaOH, KOH, Li2CO3, Na2CO3, K2CO3, CH3COOLi, CH3COONa, CH3COOK, LiCl, NaCl and KCl; The positive electrode material is one or more of N x MO2, N x M2O4 and N[N y M 1-y O2, where 0 < x < 1.05, M is one or more of Ni, Co, Mn, Fe, Nb, Ti, V, Mo, and Cr, N is Li, Na, or K, and 0 < y < 1.
2. The method for preparing the ferroelectric modified positive electrode material according to claim 1, characterized in that: The ball milling time is 1-24 h, and the ball-to-material mass ratio is (1-200):
1.
3. The method for preparing the ferroelectric modified positive electrode material according to claim 1, characterized in that: The mass ratio of the ferroelectric material to the metal oxide precursor or the positive electrode material is (0.01~10):
1.
4. The method for preparing the ferroelectric modified positive electrode material according to claim 1, characterized in that: The heat treatment is carried out in air or oxygen atmosphere, the heat treatment temperature is 300-1200°C, and the time is 5-48 hours.
5. A ferroelectric modified positive electrode material obtained by the preparation method according to any one of claims 1 to 4.
6. A secondary battery, characterized in that: Includes the ferroelectric modified positive electrode material as described in claim 5.
Citation Information
Patent Citations
Wrapping method of nickel-cobalt-aluminum ternary positive electrode material and application
CN108807964A
Method of manufacturing positive material for lithium ion battery and electrode material manufactured by the same
JP2016149270A